Acclimation responses to high light by Guazuma ulmifolia Lam. (Malvaceae) leaves at different stages of development. (15th July 2017) - Calzavara, A. K.; Rocha, J. S.; Lourenço, G.; Sanada, K.; Medri, C.; Bianchini, E.; Pimenta, J. A.; Stolf‐Moreira, R.; Oliveira, H. C.
Abstract: The re‐composition of deforested environments requires the prior acclimation of seedlings to full sun in nurseries. Seedlings can overcome excess light either through the acclimation of pre‐existing fully expanded leaves or through the development of new leaves that are acclimated to the new light environment. Here, we compared the acclimation capacity of mature (MatL, fully expanded at the time of transfer) and newly expanded (NewL, expanded after the light shift) leaves of Guazuma ulmifolia Lam. (Malvaceae) seedlings to high light. The seedlings were initially grown under shade and then transferred to full sunlight. MatL and NewL were used for chlorophyll fluorescence and gas exchange analyses, pigment extraction and morpho‐anatomical measurements. After the transfer of seedlings to full sun, the MatL persisted and acclimated to some extent to the new light condition, since they underwent alterations in some morpho‐physiological traits and maintained a functional electron transport chain and positive net photosynthesis rate. However, long‐term exposure to high light led to chronic photoinhibition in MatL, which could be related to the limited plasticity of leaf morpho‐anatomical attributes. However, the NewL showed a high capacity to use the absorbed energy in photochemistry and dissipate excess energy harmlessly, attributes that were favoured by the high structural plasticity exhibited by these leaves. Both the maintenance of mature, photosynthetically active leaves and the production of new leaves with a high capacity to cope with excess energy were important for acclimation of G. ulmifolia seedlings.